Marketplaces and Morality in Papua New Guinea: Place, Personhood and Exchange. Issue 2 (9th July 2019) - Busse, Mark; Sharp, Timothy L. M.
ABSTRACT: In Papua New Guinea (PNG) more rural people, and especially rural women, earn cash from selling in marketplaces than from any other source. PNG's marketplaces are critical for food security, and for the redistribution of wealth. They are also important meeting places where people gather to see friends, hear the latest news, attend court cases, play cards and be entertained. This introduction to this special issue on 'Marketplaces and Morality in Papua New Guinea' reviews the history of PNG marketplaces and their contemporary forms. It charts their transformation from introduced colonial spaces into dynamic Melanesian places, which, as places to buy, sell and socialise, have become pervasive institutions in the lives of both urban and rural Papua New Guineans, and places where people interact with both known and unknown others. From this, marketplaces emerge as important spaces of moral evaluation and contestation in relation to what constitutes morally acceptable exchange and what practices are acceptable in these places. The paper demonstrates that exchange in the marketplace should not be reduced to commodity transactions, and questions assumptions about the types of people marketplaces create. It argues that the country's marketplaces are productive sites to consider ideas of exchange, social relations and social personhood, and that there is a critical need to understand the concrete details of what takes place in contemporary marketplaces. Abstract :